Sodium-ion battery positive electrode material, preparation method and secondary battery
Patent Information
- Application Number
- CN202310955999.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
[0004]但在现有技术中,钠离子层状正极材料在充放电过程中易发生不可逆相变、空位有序重排、过渡金属溶解等现象,进而导致电压衰减较快、容量保持率较低,影响钠离子二次电池的循环性能、电压平台和产品良率,限制了其进一步发展
[0018] This application provides a sodium ion battery positive electrode material, preparation method and secondary battery. The positive electrode material includes a matrix material and a carbon material coated on the surface of the matrix material. The chemical formula of the matrix material is: Na 0.7 Mn 0.67-x Ti x Ni 0.33-y- z Li y Mg z O 2 , 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, the manganese source of the matrix material is selected from trimanium tetroxide; based on the mass of the positive electrode material of sodium ion battery, the mass percentage content of carbon material is 5 wt%. To 10 wt%; the coating thickness of the carbon material is 100 nm to 300 nm. This application regulates the manganese source of the matrix material selected from trimanium tetraoxide, and uses the coordinated doping of titanium elements, lithium elements and magnesium elements at different sites of the cathode material to make the cathode material have better structural stability; The synergistic effect of the coating structure design and material selection makes the positive electrode material have a stable high potential platform, a higher capacity retention rate and a higher discharge specific capacity. Applying the positive electrode material to the secondary battery is conducive to improving the secondary. While the cycling performance of the secondary battery is improved, the energy density and voltage platform of the secondary battery are improved.
Smart Images

Figure CN119447169A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a sodium ion battery positive electrode material, a preparation method and a secondary battery. Background Art
[0002] With the rapid development of new energy in recent years, the uneven distribution of lithium resources around the world and the difficulty of meeting people's needs have seriously restricted the widespread application of lithium-ion batteries. The sodium-ion battery system provides a new option for electrochemical energy storage, especially large-scale energy storage, due to its abundant resources, low price, environmental friendliness, and excellent electrochemical properties.
[0003] Among the many sodium-ion battery positive electrode materials, layered positive electrode materials have attracted widespread attention due to their higher theoretical specific capacity, simpler and greener preparation methods, low price and wide sources.
[0004] However, in the prior art, sodium ion layered cathode materials are prone to irreversible phase change, orderly rearrangement of vacancies, dissolution of transition metals, etc. during the charge and discharge process, which leads to rapid voltage decay and low capacity retention, affecting the cycle performance, voltage platform and product yield of sodium ion secondary batteries, limiting their further development. Therefore, it is urgent to develop a sodium ion battery cathode material with high capacity, high voltage and high cycle stability. Summary of the invention
[0005] The purpose of this application is to provide a sodium ion battery positive electrode material, a preparation method and a secondary battery, so that the sodium ion battery positive electrode material has a stable high potential platform, a high capacity retention rate and a high discharge specific capacity. The specific technical solution is as follows:
[0006] The first aspect of the present application provides a sodium ion battery positive electrode material, which includes a base material and a carbon material coated on the surface of the base material. The chemical formula of the base material is: Na 0.7 Mn 0.67-x Ti x Ni 0.33-y- z Li y Mg zO2, 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, the manganese source of the matrix material is selected from manganese tetraoxide, based on the mass of the sodium ion battery positive electrode material, the mass percentage of the carbon material is 5wt% to 10wt%, and the coating thickness of the carbon material is 100nm to 300nm. Through the synergistic effect of the above-mentioned coating structure design and material selection, the sodium ion battery positive electrode material has a stable high potential platform, a high capacity retention rate and a high discharge specific capacity. The positive electrode material is applied to the secondary battery, which is beneficial to improve the cycle performance of the secondary battery while improving the energy density and voltage platform of the secondary battery.
[0007] In some embodiments of the present application, the volume average particle size Dv50 of the positive electrode material of the sodium ion battery is 2 μm to 10 μm. By regulating the volume average particle size Dv50 of the positive electrode material of the sodium ion battery within the above range, it is beneficial to improve the electrochemical and mechanical properties of the positive electrode material, shorten the diffusion path of sodium ions in the positive electrode material crystal, and enable the positive electrode material to have sufficient active surface, thereby improving the cycle performance and rate performance of the secondary battery.
[0008] In some embodiments of the present application, the sodium source of the matrix material is selected from at least one of sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium citrate or sodium chloride. By selecting the above materials as the sodium source of the matrix material, it is beneficial for sodium ions to diffuse uniformly in the layered structure of the positive electrode material to form a sodium ion layer, thereby improving the reversible specific capacity of the positive electrode material.
[0009] In some embodiments of the present application, the titanium source of the matrix material is selected from at least one of titanium dioxide, titanium trioxide or titanium tetrachloride. By selecting the above materials as the titanium source of the matrix material, it is beneficial to increase the redox potential of the matrix material, inhibit the lattice change during the cycle process, reduce the number of phase changes, and thus increase the voltage platform of the secondary battery.
[0010] In some embodiments of the present application, the nickel source of the matrix material is selected from at least one of nickel oxide, nickel carbonate, nickel chloride or nickel acetate. By selecting the above materials as the nickel source of the matrix material, it is beneficial to increase the sodium deintercalation capacity of the matrix material, thereby increasing the energy density of the secondary battery.
[0011] In some embodiments of the present application, the lithium source of the matrix material is selected from at least one of lithium carbonate, lithium hydroxide, lithium acetate or lithium oxalate. By selecting the above materials as the lithium source of the matrix material, it is beneficial to uniformly dope lithium ions into the matrix material, improve the electronic conductivity and ionic conductivity of the matrix material, smooth the charge and discharge curve of the secondary battery, and improve the cycle performance of the secondary battery; at the same time, the lithium element exists in the transition metal layer of the layered structure, which is beneficial to reduce the volume change of the main structure of the positive electrode material during the charge and discharge process, and improve the structural stability of the positive electrode material.
[0012] In some embodiments of the present application, the magnesium source of the matrix material is selected from at least one of magnesium oxide, magnesium carbonate, magnesium chloride, magnesium hydroxide, magnesium oxalate or magnesium sulfate. By selecting the above materials as the magnesium source of the matrix material, it is beneficial for the magnesium element to be uniformly doped into the layered oxide, and the low-valent magnesium element Mg 2+ The doping is beneficial to maintaining the manganese element in the matrix material in a high valence state, reducing the distortion of the manganese element caused by the Jan-Taylor effect, inhibiting the harmful phase change of the matrix material under high voltage, and thereby improving the structural stability and reversible specific capacity of the positive electrode material.
[0013] In some embodiments of the present application, the carbon source of the carbon material is selected from at least one of glucose, sucrose, maltose, graphene oxide, activated carbon or carbon nanotubes. The coating layer formed by selecting the above materials as the carbon source of the carbon material acts as a bridge for sodium ion embedding / de-embedding between the base material and the electrolyte, which is conducive to the uniform embedding / de-embedding of sodium ions, alleviates the volume expansion of the positive electrode material during the charging and discharging process, and improves the structural stability of the positive electrode material.
[0014] The second aspect of the present application provides a method for preparing a positive electrode material for a sodium ion battery, wherein the method comprises:
[0015] (1) According to Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg zThe sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source are weighed respectively according to the stoichiometric ratio of sodium, manganese, titanium, nickel, lithium and magnesium in O2, wherein 0.01≤x≤0.15, 0.01≤y≤0.07, and 0.01≤z≤0.07; (2) the sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source weighed above are placed in a ball mill for ball milling, wherein the ball mill speed is 200 rpm to 400 rpm, and the ball milling time is 6 h to 10 h, and then vacuum dried at 80°C for 24 h to obtain a precursor powder; (3) heating the precursor powder to 700°C in air or oxygen atmosphere at a first heating rate of 2°C to 5°C and keeping the temperature for 4 h, and then heating the precursor powder to 950°C at a second heating rate of 2°C to 5°C and keeping the temperature for 10 h to 18 h; or, heating the precursor powder to 950°C at a heating rate of 2°C to 5°C and keeping the temperature for 10 h to 18 h; (4) cooling the precursor powder to room temperature at a cooling rate of 2°C to 5°C or a natural cooling rate to obtain a matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2; (5) the matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2 and the carbon source are placed in a ball mill for ball milling, wherein the ball mill speed is 100 rpm to 300 rpm, the ball milling time is 3 h to 5 h, and then vacuum dried at 80 ° C for 12 h to obtain a mixture; (6) the mixture obtained in the above step (5) is heated to 350 ° C at a first stage heating rate of 4 ° C under a nitrogen atmosphere and kept warm for 6 h, and then heated to 700 ° C at a second stage heating rate of 4 ° C and kept warm for 4 h; then cooled to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y- z Li y Mg z O2@C. By adjusting the ball mill speed and milling time, the uniformity of metal doping is improved, which is conducive to the formation of a more stable crystal structure of the three doped metal ions of titanium, lithium and magnesium; at the same time, by adjusting the heating rate, cooling rate and holding time, it is conducive to the crystal growth of the matrix material, and a positive electrode material with uniform particle size distribution and uniform element doping is obtained.
[0016] The third aspect of the present application provides a secondary battery comprising the sodium ion battery positive electrode material described in any of the aforementioned embodiments, the secondary battery uses sodium metal as a counter electrode, and at a charge and discharge rate of 0.1C and a charge and discharge voltage range of 2.2V to 4.4V, the discharge specific capacity of the secondary battery is 145mAh / g to 192mAh / g, the discharge median voltage is 3.5V to 3.62V, and the energy density is 235Wh / kg to 308Wh / kg. The secondary battery provided by the present application has a higher voltage platform, higher energy density, and more stable cycle performance.
[0017] Beneficial effects of this application:
[0018] The present application provides a sodium ion battery positive electrode material, a preparation method and a secondary battery. The positive electrode material includes a base material and a carbon material coated on the surface of the base material. The chemical formula of the base material is: Na 0.7 Mn 0.67-x Ti x Ni 0.33-y- z Li y Mg z O2, 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, the manganese source of the matrix material is selected from manganese tetraoxide; based on the mass of the positive electrode material of the sodium ion battery, the mass percentage of the carbon material is 5wt% to 10wt%; the coating thickness of the carbon material is 100nm to 300nm. This application selects manganese tetraoxide from the manganese source of the matrix material by regulating the synergistic co-doping of titanium, lithium and magnesium elements at different sites of the positive electrode material, so that the positive electrode material has better structural stability; through the synergistic effect of coating structure design and material selection, the positive electrode material has a stable high potential platform, a high capacity retention rate and a high discharge specific capacity. The positive electrode material is applied to secondary batteries, which is beneficial to improving the cycle performance of the secondary battery while improving the energy density and voltage platform of the secondary battery.
[0019] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0021] Figure 1 The 1st and 500th cycle charge and discharge curves of the secondary battery in Example 1 of the present application;
[0022] Figure 2 is the X-ray diffraction (XRD) pattern of the base material in Example 1 of the present application;
[0023] Figure 3 This is a scanning electron microscope image of the base material in Example 1 of the present application;
[0024] Figure 4 This is a scanning electron microscope image of the base material in Example 10 of the present application;
[0025] Figure 5 This is a scanning electron microscope image of the base material in Example 11 of the present application;
[0026] Figure 6 This is a scanning electron microscope image of the base material in Example 21 of the present application;
[0027] Figure 7 Particle size test diagram of the positive electrode material in Example 1 of the present application. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application. The specific technical solutions are as follows:
[0029] The inventors have found that in the prior art, conventional sodium layered materials such as NaNiO2, NaMnO2 or Na 0.67 Ni 0.33 Mn 0.67 The charge and discharge voltage platform of materials such as O2 is relatively complex, and the sodium ion embedding and de-embedding process is highly irreversible, resulting in severe capacity decay. In related technologies, element doping is usually used to regulate the composition and crystal structure of layered metal oxide positive electrode materials for sodium ion batteries to enhance the structural stability of the positive electrode materials. However, after a period of cycling, the positive electrode materials will experience a decrease in crystal structure stability due to phase change or transition metal dissolution, and orderly rearrangement of vacancies will occur, affecting the cycle stability and diffusion and transport of sodium ions. In addition, the doped elements are prone to cause sodium ion loss, the formation of trace impurity phases, and the generation of grain boundary effects, which reduces the energy density and cycle performance of secondary batteries.
[0030] In view of this, the first aspect of the present application provides a sodium ion battery positive electrode material, the positive electrode material comprising a base material and a carbon material coated on the surface of the base material, the chemical formula of the base material is: Na 0.7 Mn 0.67-x Tix Ni 0.33-y- z Li y Mg z O2, 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, the manganese source of the matrix material is selected from manganese tetraoxide, based on the mass of the sodium ion battery positive electrode material, the mass percentage of the carbon material is 5wt% to 10wt%, and the coating thickness of the carbon material is 100nm to 300nm. The inventors have found that manganese tetraoxide has a typical spinel structure, which makes it easy to extract / embed other ions, so it has good electrical conductivity and ion transport performance. At the same time, manganese tetraoxide also has the natural advantages of abundant resources, low price and good environmental protection, and is more suitable as a manganese source for the positive electrode material of a sodium ion battery. Therefore, the present application is beneficial to improving the electrical conductivity of the positive electrode material and reducing the production cost of the positive electrode material of a sodium ion battery by regulating the manganese source of the matrix material to be selected from manganese tetraoxide; moreover, the present application is beneficial to reducing the side reactions between the positive electrode material of the sodium ion battery and the electrolyte by coating the carbon material on the surface of the matrix material and regulating the mass percentage and coating thickness of the carbon material within the above range, slowing down the corrosion of the electrolyte on the layered material, inhibiting the precipitation and dissolution of transition metals, and improving the interface stability of the positive electrode material, thereby significantly improving the cycle performance of the secondary battery.
[0031] The present application uses a nickel-manganese-based layered positive electrode material regulated by co-doping with titanium, lithium and magnesium elements. The synergistic co-doping of the three metal elements at different sites in the layered structure optimizes the process of sodium ion embedding / extraction, improves the diffusion capacity of sodium ions in the positive electrode material, and inhibits the volume change and structural distortion of the crystal during the charge and discharge process, so that the positive electrode material has a smaller volume deformation and better structural stability during the charge and discharge process, and improves the structural stability of the positive electrode material of the sodium ion battery, which is conducive to improving the capacity retention rate of the positive electrode material. In addition, when the doping amount of titanium, lithium and magnesium elements is too much, it will lead to a decrease in the capacity of the positive electrode material of the sodium ion battery. When the doping amount is too little, the effect of improving the capacity retention rate of the positive electrode material of the sodium ion battery is not significant. The present application regulates the doping amount and proportion of each element within the above range, while significantly improving the cycle stability of the positive electrode material while avoiding a significant reduction in the reversible specific capacity and potential platform of the positive electrode material. Therefore, the present application uses the synergistic effect of the above-mentioned coating structure design and material selection to make the sodium ion battery positive electrode material have a stable high potential platform, a higher capacity retention rate and a higher discharge specific capacity. The positive electrode material is applied to secondary batteries, which is beneficial to improving the cycle performance of the secondary battery while increasing the energy density and voltage platform of the secondary battery.
[0032] In some embodiments of the present application, the volume average particle size Dv50 of the positive electrode material of the sodium ion battery is 2μm to 10μm. The size of the particle size will affect the electrochemical and mechanical properties of the positive electrode material. If the particle size of the positive electrode material is too large, the density and uniformity of the positive electrode material will decrease, thereby reducing the energy density and cycle life of the secondary battery; if the particle size of the positive electrode material is too small, the side reaction between the positive electrode material and the electrolyte will increase, thereby reducing the cycle stability of the positive electrode material. The present application regulates the volume average particle size Dv50 of the positive electrode material of the sodium ion battery within the above range, so that the electrochemical and mechanical properties of the positive electrode material can be better guaranteed, shortening the diffusion path of sodium ions in the positive electrode material grains, and inhibiting the lattice change during the cycle; the side reaction between the positive electrode material and the electrolyte can also be reduced by particle size regulation, and at the same time, the positive electrode material can have sufficient active surface, thereby improving the cycle performance and rate performance of the secondary battery. Among them, the above Dv50 represents the particle size of the material in the volume-based particle size distribution, starting from the small particle size side, reaching 50% of the volume accumulation.
[0033] In some embodiments of the present application, the sodium source of the matrix material is selected from at least one of sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium citrate or sodium chloride. By selecting the above materials as the sodium source of the matrix material, it is beneficial for sodium ions to diffuse uniformly in the layered structure of the positive electrode material to form a sodium ion layer, thereby improving the reversible specific capacity of the positive electrode material.
[0034] In some embodiments of the present application, the titanium source of the matrix material is selected from at least one of titanium dioxide, titanium trioxide or titanium tetrachloride. The inventors have found that the titanium element will replace part of the manganese element, reduce the sodium interlayer spacing in the layered structure, improve the sodium ion diffusion kinetics, enhance the structural stability of the crystal, and thus improve the capacity retention rate of the positive electrode material. Moreover, by selecting the above materials as the titanium source of the matrix material, it is beneficial to increase the redox potential of the matrix material, reduce the number of phase changes in the crystal, and thus increase the voltage platform of the secondary battery.
[0035] In some embodiments of the present application, the nickel source of the matrix material is selected from at least one of nickel oxide, nickel carbonate, nickel chloride or nickel acetate. By selecting the above materials as the nickel source of the matrix material, it is beneficial to increase the sodium deintercalation capacity of the matrix material, thereby increasing the energy density of the secondary battery.
[0036] In some embodiments of the present application, the lithium source of the matrix material is selected from at least one of lithium carbonate, lithium hydroxide, lithium acetate or lithium oxalate. By selecting the above materials as the lithium source of the matrix material, it is beneficial to uniformly dope lithium ions into the matrix material, improve the electronic conductivity and ionic conductivity of the matrix material, smooth the charge and discharge curve of the secondary battery, and improve the cycle performance of the secondary battery; at the same time, the lithium element exists in the transition metal layer of the layered structure, which is beneficial to reduce the volume change of the main structure of the positive electrode material during the charge and discharge process, and improve the structural stability of the positive electrode material.
[0037] In some embodiments of the present application, the magnesium source of the matrix material is selected from at least one of magnesium oxide, magnesium carbonate, magnesium chloride, magnesium hydroxide, magnesium oxalate or magnesium sulfate. By selecting the above materials as the magnesium source of the matrix material, it is beneficial for the magnesium element to be uniformly doped into the layered oxide, and the low-valent magnesium element Mg 2+ The doping is beneficial to maintaining the high valence state of manganese in the matrix material, reducing the distortion of manganese caused by the Jan-Taylor effect, inhibiting the harmful phase change of the matrix material under high voltage, improving the structural stability and high reversible capacity of the positive electrode material, and thus improving the cycle performance of the secondary battery.
[0038] In some embodiments of the present application, the carbon source of the carbon material is selected from at least one of glucose, sucrose, maltose, graphene oxide, activated carbon or carbon nanotubes. The coating layer formed by selecting the above materials as the carbon source of the carbon material acts as a bridge for sodium ion embedding / de-embedding between the base material and the electrolyte, which is conducive to the uniform embedding / de-embedding of sodium ions, alleviates the volume expansion of the positive electrode material during the charging and discharging process, and improves the structural stability of the positive electrode material.
[0039] The second aspect of the present application provides a method for preparing a positive electrode material for a sodium ion battery, the method comprising:
[0040] (1) According to Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg zThe sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source are weighed respectively according to the stoichiometric ratio of sodium, manganese, titanium, nickel, lithium and magnesium in O2, wherein 0.01≤x≤0.15, 0.01≤y≤0.07, and 0.01≤z≤0.07; (2) the sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source weighed above are placed in a ball mill for ball milling, wherein the ball mill speed is 200 rpm to 400 rpm, and the ball milling time is 6 h to 10 h, and then vacuum dried at 80°C for 24 h to obtain a precursor powder; (3) heating the precursor powder to 700°C in air or oxygen atmosphere at a first heating rate of 2°C to 5°C and keeping the temperature for 4 h, and then heating the precursor powder to 950°C at a second heating rate of 2°C to 5°C and keeping the temperature for 10 h to 18 h; or, heating the precursor powder to 950°C at a heating rate of 2°C to 5°C and keeping the temperature for 10 h to 18 h; (4) cooling the precursor powder to room temperature at a cooling rate of 2°C to 5°C or a natural cooling rate to obtain a matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2; (5) the matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2 and the carbon source are placed in a ball mill for ball milling, wherein the ball mill speed is 100 rpm to 300 rpm, the ball milling time is 3 h to 5 h, and then vacuum dried at 80 ° C for 12 h to obtain a mixture; (6) the mixture obtained in the above step (5) is heated to 350 ° C at a first stage heating rate of 4 ° C under a nitrogen atmosphere and kept warm for 6 h, and then heated to 700 ° C at a second stage heating rate of 4 ° C and kept warm for 4 h; then cooled to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y- z Li y Mg z O2@C.
[0041] Among them, in each embodiment and comparative example of the present application, when weighing the sodium source and the lithium source in step (1), an additional excess of 5 mol% is required based on the molar amount of the original sodium source and the lithium source to appropriately compensate for the element loss during the sintering of the precursor powder in step (3).
[0042] This application uses the above-mentioned solid phase sintering method to make each raw material diffuse mutually at high temperature to form a stable layered oxide material. The environmental conditions and process flow required for the preparation method are relatively simple, and it is easy to achieve large-scale production. Compared with the liquid phase reaction environment and subsequent experimental steps such as drying and secondary calcination required by the sol-gel method and coprecipitation method, the preparation method of this application only needs to mix the raw materials in the required proportion by ball milling, and then the positive electrode material can be obtained by high-temperature roasting. The production efficiency is high, and the various elements required by this application are abundant in reserves and the raw materials are easy to obtain, which has obvious cost advantages. At the same time, this application improves the uniformity of element doping by regulating the ball mill speed and ball milling time, which is conducive to the formation of a more stable crystal structure of the three doped metal elements of titanium, lithium and magnesium; at the same time, by regulating the heating rate, cooling rate and insulation time, it is conducive to the crystal growth of the matrix material, and obtains a positive electrode material with uniform particle size distribution and uniform element doping, and improves the structural stability of the positive electrode material, thereby improving the cycle performance of the secondary battery.
[0043] The third aspect of the present application provides a secondary battery comprising the sodium ion battery positive electrode material described in any of the aforementioned embodiments, the secondary battery uses sodium metal as a counter electrode, and at a charge and discharge rate of 0.1C and a charge and discharge voltage range of 2.2V to 4.4V, the discharge specific capacity of the secondary battery is 145mAh / g to 192mAh / g, the discharge median voltage is 3.5V to 3.62V, and the energy density is 235Wh / kg to 308Wh / kg. The secondary battery provided by the present application has a higher voltage platform, higher energy density, and more stable cycle performance.
[0044] The secondary battery of the present application also includes a separator, and the present application has no particular restrictions on the separator, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to at least one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), cellulose, polyimide (PI) or polyamide; the type of the separator may include but is not limited to at least one of a dry film, a microporous film, a composite film, a rolled film or a spun film.
[0045] The secondary battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio to obtain a non-aqueous organic solvent, and then sodium salt is added to dissolve and mix evenly. The present application has no particular restrictions on the above-mentioned "mass ratio", as long as the purpose of the present application can be achieved. The present application has no restrictions on the type of sodium salt, as long as the purpose of the present application can be achieved. For example, the sodium salt may include at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetraphenylborate [NaB(C6H5)4], sodium trifluoromethylsulfonate (NaCF3SO3), sodium fluorosilicate (NaSiF6), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium bis(oxalate)borate (NaBOB) or sodium difluorooxalateborate (NaDFOB). The present application has no particular restrictions on the concentration of the sodium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the sodium salt is 1.0 mol / L to 2.0 mol / L.
[0046] The positive electrode sheet of the present application may include a positive electrode material layer and a positive electrode current collector. The positive electrode material layer of the present application may also include a conductive agent and a binder. The conductive agent includes at least one of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, nanocarbon fibers or graphene. The binder includes at least one of polyvinylidene fluoride, sodium polyacrylate, polyvinyl pyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polypropylene. The present application does not particularly limit the mass ratio of the positive electrode material, the conductive agent and the binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs as long as the purpose of the present application can be achieved. For example, the mass ratio of the positive electrode material, the conductive agent and the binder in the positive electrode material layer is (70-95): (5-10): (5-10).
[0047] The present application has no special restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector, etc. The present application has no special restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5μm to 20μm. In the present application, the positive electrode active material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. It should be noted that the "surface" here can be the entire area of the positive electrode current collector or a partial area of the positive electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.
[0048] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: dispersing the active material, the conductive agent and the binder in N-methylpyrrolidone (NMP) solvent to form a uniform positive electrode slurry, coating the positive electrode slurry on the positive electrode collector, drying, cold pressing, cutting, slitting and re-drying to obtain a positive electrode sheet.
[0049] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include aluminum foil, copper foil, stainless steel foil or a composite current collector. The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 1 μm to 10 μm.
[0050] The present application has no particular restrictions on the structure of the secondary battery, as long as the purpose of the present application can be achieved. For example, the secondary battery structure includes but is not limited to a soft-pack sodium ion battery, a square hard-shell battery or a cylindrical hard-shell battery.
[0051] The present application does not particularly limit the preparation method of the secondary battery, and the preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the secondary battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and folding them as needed to obtain an electrode assembly with a folded structure, placing the electrode assembly in an aluminum-plastic film packaging bag, injecting the electrolyte into the packaging bag, and undergoing vacuum packaging, standing, forming, and shaping processes to obtain a soft-pack secondary battery; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet, and then winding them into an electrode assembly, then loading the electrode assembly into a steel shell, removing moisture to obtain a dry electrode assembly, and then injecting the electrolyte into the dry electrode assembly, and undergoing vacuum packaging, standing, and forming processes to obtain a cylindrical secondary battery.
[0052] Example
[0053] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0054] Test methods and equipment:
[0055] Scanning electron microscope test of positive electrode materials:
[0056] After grinding the positive electrode material, it is tested by scanning electron microscope (SEM). The instrument's focused electron beam is used to excite the sample surface to generate secondary electrons, backscattered electrons, characteristic X-rays and other secondary information, which are collected and detected for the analysis of the microscopic morphology and micro-area composition of the material surface. The test conditions of SEM are: working distance 10mm to 30mm, objective lens aperture 50μm to 500μm, acceleration voltage 10kV to 20kV, and the test instrument model is Hitachi S3400.
[0057] Cathode material particle size test:
[0058] The particle size test method refers to GB / T 19077-2016. The Dv50 of the positive electrode material of the sodium ion battery is tested using a laser particle size analyzer. During the test, when the laser beam passes through the dispersed particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The refractive index of the particles used in the test is 2.61. One sample is tested three times, and the particle size is finally measured as the average of the three tests to obtain the Dv50. Laser particle size analyzer model: FBS-1570ZXP, test range 0.1μm to 500μm.
[0059] XRD test of matrix material:
[0060] The base materials prepared in each embodiment and each comparative example were ground and transferred to a glass slide stage, and then transferred to an X-ray diffractometer (model: Shimadzu XRD-6000) for scanning testing. The test conditions were: scanning range of 10° to 80°, scanning speed of 5° / min, target material of Cu, tube current of 40 mA, and tube voltage of 40 kV.
[0061] Secondary battery 0.1C first charge and discharge specific capacity test:
[0062] The sodium ion secondary batteries in each embodiment and each comparative example were subjected to charge and discharge tests using a LAND series battery test system (LANDCT3002A): the batteries were charged at a constant current rate of 0.1C (1C = 173 mAh / g) at room temperature until the voltage reached 4.4V, and then charged at a constant voltage of 4.4V until the current was less than 0.05C, so that the batteries were in a fully charged state of 4.4V, and the obtained capacity was recorded as the 0.1C first charge specific capacity; subsequently, the batteries were discharged at a constant current rate of 0.1C until the voltage reached 2.2V, and the obtained capacity was recorded as the 0.1C first discharge specific capacity.
[0063] Secondary battery 0.1C discharge energy density test:
[0064] The sodium ion secondary batteries in each embodiment and each comparative example were subjected to charge and discharge tests using a blue electric series battery test system (LANDCT3002A): charged at a constant current of 0.1C rate at room temperature until the voltage reached 4.4V, then charged at a constant voltage of 4.4V until the current was less than 0.05C, so that it was in a 4.4V full charge state, and then discharged at a constant current of 0.1C rate until the voltage was 2.2V, and the 0.1C discharge specific capacity and the discharge median voltage were recorded. Then the 0.1C discharge energy density of the sodium ion secondary battery was calculated according to the formula: energy density (Wh / kg) = 0.1C discharge specific capacity (mAh / g) × discharge median voltage (V) / the mass sum of the positive electrode and the negative electrode (kg).
[0065] Secondary battery cycle performance test:
[0066] The sodium ion secondary batteries in each embodiment and each comparative example were repeatedly charged and discharged using a LAND series battery test system (LANDCT3002A): charged at a constant current of 0.1C at room temperature until the voltage reached 4.4V, further charged at a constant voltage of 4.4V until the current was less than 0.05C, so that it was in a 4.4V full charge state, and then discharged at a constant current of 0.1C until the voltage stopped at 2.2V. The obtained capacity was recorded as the discharge specific capacity of the first cycle, and then the above steps were repeated for 500 charge and discharge cycles, and the discharge specific capacity of the 500th cycle was recorded. Cycle capacity retention rate = (discharge specific capacity of the 500th cycle / discharge specific capacity of the first cycle) × 100%.
[0067] Example 1
[0068] <Preparation of positive electrode material>
[0069] (1) According to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are: 0.2 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium carbonate (Na2CO3), 0.07 mol titanium dioxide (TiO2), 0.27 mol nickel oxide (NiO), 0.016 mol lithium carbonate (Li2CO3) and 0.03 mol magnesium oxide (MgO) are weighed respectively;
[0070] (2) placing the manganese tetraoxide, sodium carbonate, titanium dioxide, nickel oxide, lithium carbonate and magnesium oxide weighed above into a ball mill for ball milling at a speed of 300 rpm for 8 h, and then vacuum drying at 80 ° C for 24 h to obtain a precursor powder;
[0071] (3) heating the precursor powder to 700°C in an oxygen atmosphere at a first heating rate of 3.5°C and keeping the temperature for 4 h, and then heating the precursor powder to 950°C at a second heating rate of 3.5°C and keeping the temperature for 15 h;
[0072] (4) After cooling to room temperature at a cooling rate of 3.5°C, the matrix material Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 O2;
[0073] (5) Weigh 9.3 g of base material and 1.75 g of glucose (molecular formula C6H 12 O6) was placed in a ball mill for ball milling, wherein the ball mill speed was 200 rpm, the ball milling time was 4 h, and then vacuum dried at 80 ° C for 12 h to obtain a mixture;
[0074] (6) The mixture was heated to 350°C at a first heating rate of 4°C and kept at that temperature for 6 h under the protection of a high-purity N2 atmosphere, and then heated to 700°C at a second heating rate of 4°C and kept at that temperature for 4 h; then cooled to room temperature at a natural cooling rate to obtain the positive electrode material Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 O2@C, where the Dv50 of the positive electrode material is 4.6μm and the coating thickness of the carbon material is 200nm.
[0075] <Preparation of positive electrode sheet>
[0076] The positive electrode material, polyvinylidene fluoride (PVDF) and conductive carbon black (SP) prepared above are mixed in a mass ratio of 80:10:10, and N-methylpyrrolidone (NMP) is added as a solvent. After stirring evenly, it is coated on one surface of the positive electrode current collector aluminum foil, and then placed in a blast oven at 80°C for air drying for 2 hours, and then placed in a vacuum oven at 80°C for vacuum drying for 24 hours, and finally punched out with a button battery slicer equipped with a punching die with a diameter of 10 mm to obtain a positive electrode sheet.
[0077] <Preparation of Electrolyte>
[0078] In a glove box protected by inert argon gas and with water and oxygen content <0.1ppm, 1 mol / L sodium hexafluorophosphate (NaPF6) was dissolved in an organic solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 and mixed evenly to obtain an electrolyte.
[0079] <Preparation of Separator>
[0080] A porous polypropylene film with a thickness of 16 μm was used.
[0081] <Preparation of Sodium Ion Batteries>
[0082] In a glove box protected by inert argon gas with water and oxygen content <0.1ppm, button cells were assembled in the order of negative electrode shell, metallic sodium sheet (thickness 0.2mm, analytical grade), electrolyte, diaphragm, electrolyte, positive electrode sheet, gasket, spring sheet, and positive electrode shell. Finally, they were packaged using a button cell packaging machine to obtain the CR2032 button sodium ion battery used in the test.
[0083] Example 2
[0084] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.66 Ti 0.01 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.22 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium carbonate (Na2CO3), 0.01 mol titanium dioxide (TiO2), 0.27 mol nickel oxide (NiO), 0.016 mol lithium carbonate (Li2CO3) and 0.03 mol magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0085] Example 3
[0086] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.52 Ti 0.15 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.173 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium carbonate (Na2CO3), 0.15 mol titanium dioxide (TiO2), 0.27 mol nickel oxide (NiO), 0.016 mol lithium carbonate (Li2CO3) and 0.03 mol magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0087] Example 4
[0088] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.3 1Li 0.01 Mg 0.01 The stoichiometric ratios of the sodium element, manganese element, titanium element, nickel element, lithium element and magnesium element in O2 are as follows: 0.2 mol of manganese tetraoxide (Mn3O4), 0.368 mol of sodium carbonate (Na2CO3), 0.07 mol of titanium dioxide (TiO2), 0.31 mol of nickel oxide (NiO), 0.005 mol of lithium carbonate (Li2CO3) and 0.01 mol of magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0089] Example 5
[0090] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.1 9Li 0.07 Mg 0.07 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.2 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium carbonate (Na2CO3), 0.07 mol titanium dioxide (TiO2), 0.19 mol nickel oxide (NiO), 0.037 mol lithium carbonate (Li2CO3) and 0.07 mol magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0091] Example 6
[0092] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.66 Ti 0.01 Ni 0.31 Li 0.01 Mg 0.01 The stoichiometric ratios of the sodium element, manganese element, titanium element, nickel element, lithium element and magnesium element in O2 are as follows: 0.22 mol of manganese tetraoxide (Mn3O4), 0.368 mol of sodium carbonate (Na2CO3), 0.01 mol of titanium dioxide (TiO2), 0.31 mol of nickel oxide (NiO), 0.005 mol of lithium carbonate (Li2CO3) and 0.01 mol of magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0093] Example 7
[0094] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.52 Ti 0.15 Ni 0.19 Li 0.07 Mg 0.07 The stoichiometric ratios of the sodium element, manganese element, titanium element, nickel element, lithium element and magnesium element in O2 are as follows: 0.173 mol of manganese tetraoxide (Mn3O4), 0.368 mol of sodium carbonate (Na2CO3), 0.15 mol of titanium dioxide (TiO2), 0.19 mol of nickel oxide (NiO), 0.037 mol of lithium carbonate (Li2CO3) and 0.07 mol of magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0095] Example 8
[0096] In addition to adjusting the mass percentage of the carbon material to 5 wt % as shown in Table 1 in <Preparation of positive electrode material>, the process in step (5) is adjusted to "weigh 9.5 g of the matrix material and 1.25 g of glucose (molecular formula C6H 12 O6)", so that except for the "coating thickness of the carbon material is 100nm" in step (6), the rest are the same as Example 1.
[0097] Example 9
[0098] In addition to adjusting the mass percentage of the carbon material to 10 wt % as shown in Table 1 in <Preparation of positive electrode material>, the process in step (5) is adjusted to "weigh 9 g of the matrix material and 2.5 g of glucose (molecular formula C6H 12O6)", so that except for "the coating thickness of the carbon material in step (6) is 300nm", the rest are the same as Example 1.
[0099] Example 10
[0100] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, step (3) is adjusted to "heat the precursor powder to 700°C at a first heating rate of 3.5°C under an oxygen atmosphere and keep it warm for 4 hours, and then heat it to 950°C at a second heating rate of 3.5°C and keep it warm for 10 hours", so that "Dv50 of the positive electrode material is 2μm" in step (6) as shown in Table 1, the rest is the same as Example 1.
[0101] Embodiment 11
[0102] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, step (3) is adjusted to "heat the precursor powder to 700°C at a first heating rate of 3.5°C under an oxygen atmosphere and keep it warm for 4 hours, and then heat it to 950°C at a second heating rate of 3.5°C and keep it warm for 18 hours", so that "Dv50 of the positive electrode material is 10μm" in step (6) as shown in Table 1, the rest is the same as Example 1.
[0103] Example 12
[0104] In addition to adjusting the raw material types of each element as shown in Table 1 in <Preparation of positive electrode materials>, that is, adjusting step (1) to "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are respectively weighed 0.2 mol manganese tetraoxide (Mn3O4), 0.735 mol sodium hydroxide (NaOH), 0.07 mol titanium dioxide (TiO2), 0.27 mol nickel oxide (NiO), 0.016 mol lithium carbonate (Li2CO3) and 0.03 mol magnesium carbonate (MgCO3)"; the process in the control step (5) is "weighing 9.3 g of the matrix material and 1.67 g of sucrose (molecular formula C 12 H 22 O 11 Except for " ), the rest are the same as in Example 1.
[0105] Example 13
[0106] In addition to adjusting the raw material types of each element as shown in Table 1 in <Preparation of positive electrode materials>, that is, adjusting step (1) to "according to Na 0.7 Mn 0.6Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratio of sodium, manganese, titanium, nickel, lithium and magnesium in O2 is as follows: 0.2 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium oxide (Na2O), 0.07 mol titanium dioxide (TiO2), 0.27 mol nickel oxide (NiO), 0.016 mol lithium carbonate (Li2CO3) and 0.03 mol magnesium chloride (MgCl2) are weighed respectively; the process in the control step (5) is as follows: "9.3 g of the matrix material and 0.85 g of graphene oxide (molecular formula C 140 H 42 O 20 Except for " ), the rest are the same as in Example 1.
[0107] Embodiment 14
[0108] In addition to adjusting the raw material types of each element as shown in Table 1 in <Preparation of positive electrode materials>, that is, adjusting step (1) to "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are respectively weighed 0.2 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium peroxide (Na2O2), 0.07 mol titanium dioxide (TiO2), 0.27 mol nickel carbonate (NiCO3), 0.037 mol lithium hydroxide (LiOH) and 0.03 mol magnesium hydroxide [Mg(OH)2]"; the process in the control step (5) is "weighing 9.3 g of the base material and 1.67 g of maltose (molecular formula C 12 H 22 O 11 Except for " ), the rest are the same as in Example 1.
[0109] Embodiment 15
[0110] In addition to adjusting the raw material types of each element as shown in Table 1 in <Preparation of positive electrode materials>, that is, adjusting step (1) to "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.2 mol of manganese tetraoxide (Mn3O4), 0.245 mol of sodium citrate (C6H5Na3O7), 0.035 mol of titanium trioxide (Ti2O3), 0.27 mol of nickel chloride (NiCl2), 0.032 mol of lithium acetate (CH3COOLi) and 0.03 mol of magnesium oxalate (MgC2O4) are weighed respectively"; except that the process in the control step (5) is "weighing 9.3 g of the matrix material and 0.7 g of activated carbon (molecular formula C)", the rest are the same as in Example 1.
[0111] Example 16
[0112] In addition to adjusting the raw material types of each element as shown in Table 1 in <Preparation of positive electrode materials>, that is, adjusting step (1) to "according to Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.2 mol manganese tetraoxide (Mn3O4), 0.735 mol sodium chloride (NaCl), 0.035 mol titanium tetrachloride (TiCl4), 0.27 mol nickel acetate [Ni(CH3COO)2], 0.032 mol lithium oxalate (Li2C2O4) and 0.03 mol magnesium sulfate (MgSO4) are weighed respectively"; except that the process in the regulating step (5) is "weighing 9.3 g of the matrix material and 0.7 g of the carbon nanotubes (molecular formula C)", the rest are the same as in Example 1.
[0113] Embodiment 17
[0114] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 700°C in an oxygen atmosphere at a first heating rate of 2°C and keeping it warm for 4 hours, and then heating it to 950°C at a second heating rate of 2°C and keeping it warm for 15 hours", the rest is the same as Example 1.
[0115] Embodiment 18
[0116] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 700°C in an oxygen atmosphere at a first heating rate of 5°C and keeping it warm for 4 hours, and then heating it to 950°C at a second heating rate of 5°C and keeping it warm for 15 hours", the rest is the same as Example 1.
[0117] Embodiment 19
[0118] In addition to the step (4) of "cooling to room temperature at a natural cooling rate to obtain the matrix material Na 0.7 Mn 0.6 Ti 0.07 Ni 0.27 Li 0.03 Mg 0.03 Except for O2", the rest are the same as in Example 1.
[0119] Embodiment 20
[0120] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 700°C in an air atmosphere at a first heating rate of 3.5°C and keeping it warm for 4 hours, and then heating it to 950°C at a second heating rate of 3.5°C and keeping it warm for 15 hours", the rest is the same as Example 1.
[0121] Embodiment 21
[0122] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 950°C at a heating rate of 3.5°C under an oxygen atmosphere and keeping it warm for 15 hours", the rest is the same as Example 1.
[0123] Embodiment 22
[0124] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 950°C at a heating rate of 3.5°C under an oxygen atmosphere and keeping it warm for 10 hours", the rest is the same as Example 1.
[0125] Embodiment 23
[0126] Except that in <Preparation of Positive Electrode Material>, as shown in Table 2, the control step (3) is "heating the precursor powder to 950°C at a heating rate of 3.5°C under an oxygen atmosphere and keeping it warm for 18 hours", the rest is the same as Example 1.
[0127] Embodiment 24
[0128] Except that in <Preparation of Positive Electrode Materials>, as shown in Table 2, the ball mill speed when mixing the raw materials of the matrix material in step (2) is 200 rpm and the ball milling time is 6 h; the ball mill speed when mixing the matrix material and the carbon source in step (5) is 100 rpm and the ball milling time is 3 h, the rest is the same as Example 1.
[0129] Embodiment 25
[0130] Except that in <Preparation of Positive Electrode Materials>, as shown in Table 2, the ball mill speed when mixing the raw materials of the matrix material in step (2) is 400 rpm and the ball milling time is 10 h; the ball mill speed when mixing the matrix material and the carbon source in step (5) is 300 rpm and the ball milling time is 5 h, the rest is the same as Example 1.
[0131] Comparative Example 1
[0132] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.67 Ni 0.33 The stoichiometric ratios of sodium, manganese and nickel in O2 are as follows: 0.223 mol manganese tetraoxide (Mn3O4), 0.368 mol sodium carbonate (Na2CO3) and 0.33 mol nickel oxide (NiO) are weighed respectively. The rest are the same as in Example 1.
[0133] Comparative Example 2
[0134] Except in <Preparation of positive electrode material>, as shown in Table 1, the control step (1) is "according to Na 0.7 Mn 0.37 Ti 0.3 Ni 0.1 1Li 0.11 Mg 0.11 The stoichiometric ratios of sodium, manganese, titanium, nickel, lithium and magnesium in O2 are as follows: 0.123 mol of manganese tetraoxide (Mn3O4), 0.368 mol of sodium carbonate (Na2CO3), 0.3 mol of titanium dioxide (TiO2), 0.11 mol of nickel oxide (NiO), 0.055 mol of lithium carbonate (Li2CO3) and 0.11 mol of magnesium oxide (MgO) are weighed respectively. The rest are the same as in Example 1.
[0135] Comparative Example 3
[0136] Except that the carbon coating process in step (5) and step (6) is not adopted in <Preparation of positive electrode material>, the rest is the same as Example 1.
[0137] Comparative Example 4
[0138] In addition to adjusting the mass percentage of the carbon material to 20 wt % as shown in Table 1 in <Preparation of positive electrode material>, the process in step (5) is adjusted to "weigh 8 g of the matrix material and 5 g of glucose (molecular formula C6H 12 O6)", so that except for "the coating thickness of the carbon material is 500nm" in step (6), the rest are the same as Example 1.
[0139] Table 1
[0140]
[0141]
[0142] Table 2
[0143]
[0144]
[0145]
[0146] Note: “ / ” in Table 1 and Table 2 indicates no relevant parameters.
[0147] Table 3
[0148]
[0149]
[0150] Referring to Tables 1 to 3, it can be seen from Examples 1 to 25 and Comparative Examples 1 to 4 that the present application selects manganese tetraoxide from manganese source by regulating the matrix material, and utilizes the synergistic co-doping of titanium, lithium and magnesium at different sites of the positive electrode material, so that the positive electrode material has better structural stability; through the synergistic effect of coating structure design and material selection, the positive electrode material of the sodium ion battery has a stable high potential platform, a high capacity retention rate and a high discharge specific capacity. The sodium ion battery positive electrode material prepared in the present application is applied to a secondary battery, which can significantly improve the cycle performance of the secondary battery and increase the voltage platform and energy density of the secondary battery.
[0151] Specifically, Figure 1 The cyclic charge and discharge performance test diagram of the button-type sodium ion battery in Example 1 at a current density of 0.1C is shown in FIG. Figure 1 It can be seen that the discharge specific capacity of the first cycle is 149 mAh / g, and the discharge specific capacity after 500 cycles is 139 mAh / g, with a capacity retention rate of 93%, indicating that it has good cycle performance, thereby indicating that the positive electrode material provided in this application is suitable for application in sodium ion secondary batteries. Figure 2 is the XRD pattern of the matrix material in Example 1, from Figure 2 It can be seen that there is a P2 phase characteristic diffraction peak with high intensity and sharp peak at 16°, and there are no other impurity phase peaks in the spectrum, indicating that the matrix material prepared in the present application has good crystallinity and high purity. Figure 3 is a scanning electron microscope image of the matrix material in Example 1, from Figure 3It can be seen that the overall structure of the matrix material is a relatively clear and complete block structure, the surface morphology is regular and dense, there are no obvious impurities, the size distribution is relatively uniform, and the block structure contains clearer layered stacking.
[0152] It can be seen from Examples 1 to 7 and Comparative Examples 1 to 2 in Table 1 and Table 3 that the present application adjusts the content and ratio of each element in the matrix material to meet the following requirements: Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2, 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, which is beneficial to improving the voltage platform and energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0153] It can be seen from Example 1, Example 8 to Example 9, and Comparative Example 3 to Comparative Example 4 in Table 1 and Table 3 that the present application helps to improve the cycle performance of the secondary battery while maintaining the energy density of the secondary battery by adjusting the mass percentage of the carbon material to 5wt% to 10wt% and the coating thickness of the carbon material to 100nm to 300nm.
[0154] It can be seen from Examples 1, 10 and 11 in Table 1 and Table 3 that the present application is beneficial to improving the discharge specific capacity and electrochemical stability of the positive electrode material of the sodium ion battery by adjusting the volume average particle size Dv50 of the positive electrode material of the sodium ion battery to 2 μm to 10 μm, thereby obtaining a secondary battery with good cycle performance and high energy density. Specifically, Figure 7 The particle size test diagram of the positive electrode material in Example 1 of the present application is as follows: Figure 7 It can be seen that the volume average particle size Dv50 of the positive electrode material is 4.6μm, and the particle size distribution width is narrow, indicating that its particle size is relatively uniform.
[0155] It can be seen from Examples 1 and 12 to 16 in Tables 1 and 3 that the present application is beneficial to obtaining a secondary battery with good cycle performance, higher energy density and higher voltage platform by regulating the types of raw materials of each element of the positive electrode material within the scope of the present application.
[0156] The heating rate, cooling rate and sintering atmosphere during the sintering of the precursor powder usually also have an impact on the performance of the secondary battery. It can be seen from Table 2 and Example 1, Example 17 to Example 20 in Table 3 that the present application is more conducive to obtaining a secondary battery with good cycle performance, higher energy density and higher voltage platform by adjusting the heating rate of the precursor powder to 3.5°C / min, the cooling rate to 3.5°C / min, and the sintering atmosphere to oxygen during the sintering.
[0157] The temperature gradient during sintering of the precursor powder will also generally affect the performance of the secondary battery. Specifically, Figure 4 is a scanning electron microscope image of the matrix material in Example 10, from Figure 4 It can be seen that the overall structure of the matrix material is relatively irregular and the size distribution is relatively uneven. Figure 5 is a scanning electron microscope image of the matrix material in Example 11, from Figure 5 It can be seen that the particles of the matrix material are relatively adherent and there is no clear edge structure. Figure 6 is a scanning electron microscope image of the matrix material in Example 21, from Figure 6 It can be seen from Table 2 and Table 3 that the particle size distribution of the matrix material is relatively uneven. It can be seen from Example 1, Example 10 to Example 11, and Example 21 to Example 23 that the present application is more conducive to obtaining a secondary battery with good cycle performance, higher energy density and higher voltage platform by regulating the temperature gradient during sintering of the precursor powder to a two-stage heating process of 700°C for 4 hours and 950°C for 15 hours.
[0158] The ball mill speed and milling time when the raw materials of the matrix material are mixed, and the ball mill speed and milling time when the matrix material is mixed with the carbon source usually also have an impact on the performance of the secondary battery. From Example 1, Example 24 to Example 25 in Table 2 and Table 3, it can be seen that by regulating the ball mill speed and milling time when the raw materials of the matrix material are mixed, and the ball mill speed and milling time when the matrix material is mixed with the carbon source within the scope of this application, it is beneficial to obtain a secondary battery with good cycle performance, higher energy density and higher voltage platform.
[0159] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusions, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the statement "include..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0160] The above are only preferred embodiments of the present application and are not intended to limit the protection scope of the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application are included in the protection scope of the present application.
Claims
1. A sodium ion battery positive electrode material, wherein: The sodium ion battery positive electrode material comprises a base material and a carbon material coated on the surface of the base material. The chemical formula of the matrix material is: Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2, 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07, the manganese source of the matrix material is selected from trimanganese tetraoxide; Based on the mass of the sodium ion battery positive electrode material, the mass percentage of the carbon material is 5wt% to 10wt%; The coating thickness of the carbon material is 100nm to 300nm.
2. The sodium ion battery positive electrode material according to claim 1, wherein The volume average particle size Dv50 of the sodium ion battery positive electrode material is 2 μm to 10 μm.
3. The sodium ion battery positive electrode material according to claim 1, wherein The sodium source of the matrix material is selected from at least one of sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium citrate or sodium chloride.
4. The sodium ion battery positive electrode material according to claim 1, wherein The titanium source of the matrix material is selected from at least one of titanium dioxide, titanium trioxide or titanium tetrachloride.
5. The sodium ion battery positive electrode material according to claim 1, wherein The nickel source of the matrix material is selected from at least one of nickel oxide, nickel carbonate, nickel chloride or nickel acetate.
6. The sodium ion battery positive electrode material according to claim 1, wherein The lithium source of the matrix material is selected from at least one of lithium carbonate, lithium hydroxide, lithium acetate or lithium oxalate.
7. The sodium ion battery positive electrode material according to claim 1, wherein The magnesium source of the matrix material is selected from at least one of magnesium oxide, magnesium carbonate, magnesium chloride, magnesium hydroxide, magnesium oxalate or magnesium sulfate.
8. The sodium ion battery positive electrode material according to claim 1, wherein The carbon source of the carbon material is selected from at least one of glucose, sucrose, maltose, graphene oxide, activated carbon or carbon nanotubes.
9. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 8, wherein: The method comprises: (1) According to Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z The stoichiometric ratio of sodium, manganese, titanium, nickel, lithium and magnesium in O2 is: weigh the sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source respectively, wherein 0.01≤x≤0.15, 0.01≤y≤0.07, 0.01≤z≤0.07; (2) placing the sodium source, manganese tetraoxide, titanium source, nickel source, lithium source and magnesium source weighed above into a ball mill for ball milling, wherein the ball mill speed is 200 rpm to 400 rpm, the ball milling time is 6 h to 10 h, and then vacuum drying at 80 ° C for 24 h to obtain a precursor powder; (3) heating the precursor powder in air or oxygen atmosphere to 700°C at a first heating rate of 2°C to 5°C and keeping the temperature for 4 hours, and then heating the precursor powder to 950°C at a second heating rate of 2°C to 5°C and keeping the temperature for 10 to 18 hours; Alternatively, the temperature is increased to 950°C at a rate of 2°C to 5°C and kept at this temperature for 10 to 18 hours; (4) cooling the temperature to room temperature at a cooling rate of 2°C to 5°C or a natural cooling rate to obtain the matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2; (5) The matrix material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2 and the carbon source are put into a ball mill and ball milled, wherein the ball mill speed is 100 rpm to 300 rpm, the ball milling time is 3 h to 5 h, and then vacuum dried at 80 ° C for 12 h to obtain a mixture; (6) The mixture obtained in step (5) is heated to 350° C. at a first stage heating rate of 4° C. and kept at this temperature for 6 h under a nitrogen atmosphere, and then heated to 700° C. at a second stage heating rate of 4° C. and kept at this temperature for 4 h; and then cooled to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material Na 0.7 Mn 0.67-x Ti x Ni 0.33-y-z Li y Mg z O2@C.
10. A secondary battery comprising the sodium ion battery positive electrode material according to any one of claims 1 to 8, wherein: The secondary battery uses sodium metal as the counter electrode. At a charge and discharge rate of 0.1C and a charge and discharge voltage range of 2.2V to 4.4V, the secondary battery has a discharge specific capacity of 145mAh / g to 192mAh / g, a discharge median voltage of 3.5V to 3.62V, and an energy density of 235Wh / kg to 308Wh / kg.